2013
DOI: 10.1021/la4027078
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Mediated Electrochemical Synthesis of Platelike Copper Crystals for Methanol Electrooxidation

Abstract: A room-temperature electrochemical approach to synthesizing anisotropic platelike copper microcrystals and nanocrystals in the presence of potassium bromide is presented. Morphological and elemental characterization was performed using SEM, TEM, and XRD to confirm the anisotropic morphology and crystal structure of the synthesized copper particles. A possible mechanism for explaining the anisotropic crystal growth is proposed on the basis of the preferential adsorption of bromide ions to selective crystal face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Besides the peaks assigned to graphite (G) and paraffin wax (W), one strong peak and two much weaker ones are present at 43. 5° [20]. The anisotropic laminated structure shown in Fig.…”
Section: Characterization Of Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the peaks assigned to graphite (G) and paraffin wax (W), one strong peak and two much weaker ones are present at 43. 5° [20]. The anisotropic laminated structure shown in Fig.…”
Section: Characterization Of Electrodesmentioning
confidence: 99%
“…Porous Cu foams can be formed at very negative applied potentials, e.g., -6 V [6] or −4 V [19] vs. Ag/AgCl/ 3 M KCl, by the assistance of strong hydrogen evolution. An anisotropic plate-like morphology of Cu NPs was acquired at 0.06 V vs. Ag/AgCl/3 M KCl for methanol electro-oxidation [20]. At a potential of −0.175 V vs. Ag/AgCl/3 M KCl the obtained were the coarse grained copper clusters [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently,ithas been reported that the {111} crystal planes of Cu and Ni have enhanced catalytic activity toward methanol oxidation. [14] As seen in Figure 1a nd the Supporting Information, Figure S1, the hierarchically structured Ni-Cu alloys composed of interconnected branches may allow the active {111} crystal plane to be fully exposed, which is favorable for the electrocatalytic oxidation reaction of methanol. Fort he XPS survey,p eaks in the full XPS spectrum indicate the existence of Cu, Ni, O, and Celements (Figure 1e;Supporting Information, Figure S6 a,c).…”
mentioning
confidence: 99%
“…Figure S7) revealed that the elemental distributions of Ni and Cu are uniform for all three samples,i ndicating that Ni and Cu are evenly distributed throughout the hierarchically structured Ni-Cu alloys.T he corresponding XRD spectrum (Supporting Information, Figure S3) confirmed the {111} planes of the hierarchically structured Ni-Cu alloys are preferentially oriented. [14] As seen in Figure 1a nd the Supporting Information, Figure S1, the hierarchically structured Ni-Cu alloys composed of interconnected branches may allow the active {111} crystal plane to be fully exposed, which is favorable for the electrocatalytic oxidation reaction of methanol. [14] As seen in Figure 1a nd the Supporting Information, Figure S1, the hierarchically structured Ni-Cu alloys composed of interconnected branches may allow the active {111} crystal plane to be fully exposed, which is favorable for the electrocatalytic oxidation reaction of methanol.…”
mentioning
confidence: 99%